Cost‐effectiveness of prospective red blood cell antigen matching to prevent alloimmunization among sickle cell patients. Issue 1 (21st May 2013) - Kacker, Seema; Ness, Paul M.; Savage, William J.; Frick, Kevin D.; Shirey, R. Sue; King, Karen E.; Tobian, Aaron A.R.
<x xml:space="preserve">Abstract</x> Background Sickle cell disease is associated with extensive health care utilization; estimated lifetime costs exceed $460, 000 per patient. Approximately 30% of chronically transfused sickle cell patients become alloimmunized to red blood cell antigens, but these patients cannot be identified a priori. Prospective antigen matching can prevent alloimmunization, but is costly and may not benefit most patients. Study Design and Methods A Markov‐based model was constructed to compare the health and financial implications of four alternative antigen‐matching strategies for chronically transfused sickle cell patients. The strategies varied by the group of patients receiving matched blood (all patients prophylactically or only patients with a history of alloimmunization [history‐based]), and by the extent of antigen matching (limited to C, E, and K, or extended to 11 antigens). Direct medical costs and alloimmunization events were assessed over 10‐ and 20‐year periods, for a hypothetical cohort of initially transfusion‐naive patients and for a dynamic population. Results Within a hypothetical cohort of initially transfusion‐naive patients, implementing prophylactic limited matching for all chronically transfused patients instead of history‐based limited matching is expected to cost an additional $765.56 million over 10 years, but result in 2072 fewer alloimmunization events. Within the same cohort, implementing prospective extensive matching is expected to cost $1.86 billion more than history‐based extensive matching, but result in 2424 fewer alloimmunization events. Averting a single alloimmunization event using prospective matching would cost $369, 482 to $769, 284. Among a dynamic population over 10 years, prospective limited matching is expected to cost $358.34 million more than history‐based limited matching. Conclusions While prospective matching for all transfused patients would reduce alloimmunization, this strategy requires considerable expenditure.